Sino-Tibetan Buddhism across the ages - Bianchi, Ester; Shen, Weirong (Studies on East Asian religions, 2021)
Introduction / Ester Bianchi and Weirong Shen -- Part I. Early Sino-Tibetan Buddhist Encounters: 1. An Invented Tradition: Hva shang Mahāyāna and His Teachings in Tibetan Literature / Weirong Shen -- 2. Attending the Elders: Icons and Identities of Dharmatāla and Hva shang across Sino-Tibetan Buddhist Milieus / Linghui Zhang -- 3. To the Place Where Tea Comes from: Gyi-ljang's Trip to China / Penghao Sun -- 4. Edicts and the Edible: Digesting Imperial Sovereignty in Lhasa / Fan Zhang -- Part II. Tibetan Tantra in the Modern World: 5. Tibetan Theosophy: Helena Blavatsky's Tantric Connection / Urs App -- 6. Tantrism, Modernity, History: On Lü Cheng's Philological Method / Martino Dibeltulo Concu -- Part III. Modern Forms of Sino-Tibetan Hybridity: 7. The Combined Practice of Vinaya and Tantra in Nenghai's Path to Liberation / Ester Bianchi -- 8. Rethinking the Perfection of Wisdom: A Chinese Interpretation of the Ornament of Realization / Wei Wu -- 9. Accidental Esoterics: Han Chinese Practicing Tibetan Buddhism / Alison Denton Jones -- 10. Tibeto-Mongol and Chinese Buddhism in Present-Day Hohhot, Inner Mongolia: Competition and Interactions / Isabelle Charleux -- Index.